Tissue at Risk and Ischemic Core Estimation Using Deep Learning in Acute Stroke - Yu, Y.; Xie, Y.; Thamm, T.; Gong, E.; Ouyang, J.; Christensen, S.; Marks, M.P.; Lansberg, M.G.; Albers, G.W.; Zaharchuk, G. (American Journal of Neuroradiology, 2021)
BACKGROUND AND PURPOSE: In acute stroke patients with large vessel occlusions, it would be helpful to be able to predict the difference in the size and location of the final infarct based on the outcome of reperfusion therapy. Our aim was to demonstrate the value of deep learning–based tissue at risk and ischemic core estimation. We trained deep learning models using a baseline MR image in 3 multicenter trials.MATERIALS AND METHODS: Patients with acute ischemic stroke from 3 multicenter trials were identified and grouped into minimal (≤20%), partial (20%-80%), and major (≥80%) reperfusion status based on 4- to 24-hour follow-up MR imaging if available or into unknown status if not. Attention-gated convolutional neural networks were trained with admission imaging as input and the final infarct as ground truth. We explored 3 approaches: 1) separate: train 2 independent models with patients with minimal and major reperfusion; 2) pretraining: develop a single model using patients with partial and unknown reperfusion, then fine-tune it to create 2 separate models for minimal and major reperfusion; and 3) thresholding: use the current clinical method relying on apparent diffusion coefficient and time-to-maximum of the residue function maps. Models were evaluated using area under the curve, the Dice score coefficient, and lesion volume difference.RESULTS: Two hundred thirty-seven patients were included (minimal, major, partial, and unknown reperfusion: n = 52, 80, 57, and 48, respectively). The pretraining approach achieved the highest median Dice score coefficient (tissue at risk = 0.60, interquartile range, 0.43–0.70; core = 0.57, interquartile range, 0.30–0.69). This was higher than the separate approach (tissue at risk = 0.55; interquartile range, 0.41–0.69; P = .01; core = 0.49; interquartile range, 0.35–0.66; P = .04) or thresholding (tissue at risk = 0.56; interquartile range, 0.42–0.65; P = .008; core = 0.46; interquartile range, 0.16–0.54; P < .001).CONCLUSIONS: Deep learning models with fine-tuning lead to better performance for predicting tissue at risk and ischemic core, outperforming conventional thresholding methods.AUCarea under the curveDSCDice score coefficientiCASImaging Collaterals in Acute StrokeIQRinterquartile rangeTmaxtime-to-maximum of the residue function